Examining Hardiness, Coping and Stress-Related Growth Following Sport Injury. Issue 2 (2nd April 2016) - Salim, Jade; Wadey, Ross; Diss, Ceri
Abstract : This study aimed to explain how injured athletes high in hardiness experienced stress-related growth and why athletes low in hardiness are less likely to derive such benefits. Twenty participants were theoretically sampled into high ( n = 10) and low ( n = 10) hardiness groups. Semistructured interviews were used for data collection. Findings revealed that athletes high in hardiness experienced stress-related growth from having an emotional outlet, which enabled them to reframe their injury and experience positive affect. In contrast, athletes low in hardiness had no emotional outlet, which led to suboptimal outcomes. These findings have important implications for practitioners working with injured athletes.